Caregiver Talk and Medical Risk as Predictors of Language Outcomes in Full Term and Preterm Toddlers. Issue 5 (28th April 2017) - Adams, Katherine A.; Marchman, Virginia A.; Loi, Elizabeth C.; Ashland, Melanie D.; Fernald, Anne; Feldman, Heidi M.
Abstract : This study examined associations between caregiver talk and language skills in full term (FT) and preterm (PT) children ( n  = 97). All‐day recordings of caregiver–child interactions revealed striking similarities in amount of caregiver talk heard by FT and PT children. Children who heard more caregiver talk at 16 months demonstrated better knowledge‐ and processing‐based language skills at 18 months. The unique contributions of caregiver talk were tempered by medical risk in PT children, especially for processing speed. However, there was no evidence that birth status or medical risk moderated the effects of caregiver talk. These findings highlight the role of caregiver talk in shaping language outcomes in FT and PT children and offer insights into links between neurodevelopmental risk and caregiver–child engagement.